Tetrandrine inhibits the proliferation of mesangial cells induced by enzymatically deglycosylated human IgA1 via IgA receptor/MAPK/NF-κB signaling pathway - Xu, Wencheng; Song, Wanci; Chen, Shuhe; Jin, Shanshan; Xue, Xue; Min, Jinwen; Wang, Xiaoqin; You, Pengtao (Frontiers in Pharmacology, 2023)
Objective: Despite the use of renin-angiotensin system blockade and immunosuppressive drugs, including corticosteroids, the current treatment regimens for Immunoglobulins A nephropathy (IgAN) are severely limited. The proliferation of mesangial cell and deposition of deglycosylated human IgA1 immune complex are the most common pathologic features of IgAN. We examined the tetrandrine potential of suppressing the proliferation of mesangial cells and explored its underlying mechanisms with a focus on IgA receptor/MAPK/NF-κB signaling pathway. Methods: Standard human IgA (native IgA) were enzymatically desialylated (deS IgA) or further degalactosylated (deS/deGal IgA) using neuraminidase and β‐galactosidase. Rat glomerular mesangial cells (HBZY-1) and human renal mesangial cells (HRMC) stimulated by IgA were used to observe the suppressive effect of tetrandrine. The MTT assay was used to detect the cell viability. The protein expression of IgA receptor/MAPK/NF-κB signaling pathway was examined by Western blot. Cell cycle analysis was measured by flow cytometer. Results: Native IgA and deS IgA showed limited stimulation effect on both HBZY-1 cells and HRMCs, whereas deS/deGal IgA significantly stimulated the proliferation of both HBZY-1 cells and HRMCs (p <0.05). Compared with non-stimulation of deS/deGal IgA, 1~3 M of tetrandrine had stronger inhibitory effect on the proliferation of HBZY-1 cells and HRMCs with the stimulation of deS/deGal IgA (p <0.05), suggesting that tetrandrine possibly inhibited the proliferation of mesangial cells induced by deglycosylated human IgA1 specifically. Molecular mechanism study revealed that tetrandrine decreased the expression of IgA1 receptor, CD71 and β4GALT1, and inhibited the activation of MAPK/NF-κB significantly (p <0.05). Moreover, these inhibitory effect of tetrandrine triggered cell cycle arrest and leaded the cell growth to stop at S phase companied with the upregulating of cyclin A2 and downregulating of cyclin D1. Conclusion: Taken together, tetrandrine inhibited the proliferation of mesangial cells induced by enzymatically deglycosylated human IgA1 via IgA receptor/MAPK/NF-κB signaling pathway. Based on these potential molecular mechanisms, tetrandrine would be an appealing therapeutic option for IgAN.